Morfoanatomia do fruto, da semente e da plântula de Ormosia paraensis Ducke - Silva, Breno Marques da Silva; Silva, Camila de Oliveira; Môro, Fabíola Vitti [UNESP]; Vieira, Roberval Daiton [UNESP] (FapUNIFESP (SciELO), 2015)
Ormosia paraensis Ducke, known as “tento”, has seeds that are used to make handcrafts and wood that is worked on by furniture makers. For forest identification and seeds technology, the information about the morphoanatomy of their fruits, seeds and seedlings is scarce. Therefore, the purpose of this study was to morphoanatomically describe the fruit, seeds and the post-seminal development of “tento”. For the morphoanatomical description, the evaluations were examined by optical and electron microscopy scanning. The fruit is a nutant legume, brown to black, dehiscent and with one or two seeds of lateral placentation, being the epicarp slim, the mesocarp woody and the endocarp spongy, measuring about 4.4 cm, 3.9 cm and 2.0 cm in length, width and thickness, respectively. The seeds are bitegmic, exalbuminous and rounded with average dimensions: length of 12.36 mm, width of 9.68 mm and thickness of 8.03 mm. The “tento” seedlings have simple and alternate leaves, with tap roots and cylindrical stem, being its germination hypogeal cryptocotyledonary.
Morphoanatomy of fruit, seed and seedling of Ormosia paraensis Ducke
Keywords: Fabaceae; Germination; Morphology; Post-seminal development